Eco-Mysticism as a Basis for Water Conservation in Sendang Tawun Ngawi - Kasanah, Nur; aizurrahman, Hilmi F; Sajjad, Muhammad Husain As (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Water conservation amid the climate crisis requires a holistic approach based on eco-mysticism that integrates ecological knowledge with cultural and spiritual values. This study examines the role of local eco-mysticism as a basis for water conservation at Sendang Tawun, Ngawi. The research focuses on ritual practices and local beliefs of the Tawun community in preserving water sources. The aim is to understand the relationship between mystical rituals, customary prohibitions, and environmental conservation efforts. The method employed is qualitative research with a case study approach through in-depth interviews, participatory observation, and documentation. Data were obtained from traditional leaders, local communities, officials, vendors, and visitors. The findings show that local eco-mysticism is manifested through the Keduk Beji ritual and prohibitions against taking turtles, fish, and plants from the spring area. These beliefs are grounded in ancestral reverence, faith in spiritual guardians, and fear of misfortune. Such practices have proven effective in sustaining water sources, preserving traditions, and promoting tourism-based economies. Thus, eco-mysticism can serve as a model of culturally rooted water conservation.